2019
DOI: 10.1021/acs.jpca.9b04372
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Excited-State Isomerization and Decay Paths in cis-Cyclobiazobenzene

Abstract: Herein we have employed OM2/MRCI-based full-dimensional nonadiabatic dynamics simulations to explore the photoisomerization and subsequent excited-state decay of a macrocyclic cyclobiazobenzene (CBA) molecule. Two S1/S0 conical intersection structures are found to be responsible for the excited-state decay. Related to these two conical intersections, we found two stereoselective photoisomerization and excited-state decay pathways, which correspond to the clockwise and counterclockwise rotation motions with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 100 publications
1
7
0
Order By: Relevance
“…This is ascribed to the fact that S1S0_SPc [S1S0_SPt] is structurally much closer to S0_SPc [S0_SPt]. This exclusive stereospecific excited-state relaxation is seen in previous studies. ,, The right panel of Figure depicts time distribution of all hopping events from S 1 to S 0 . Almost all hopping events take place within 150 fs with a maximum peak at about 60 fs, in good agreement with experimental studies. ,, Moreover, it can be found that SPc and SPt have similar distribution for the S 1 → S 0 hopping times (see red vs blue in the right panel of Figure ).…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…This is ascribed to the fact that S1S0_SPc [S1S0_SPt] is structurally much closer to S0_SPc [S0_SPt]. This exclusive stereospecific excited-state relaxation is seen in previous studies. ,, The right panel of Figure depicts time distribution of all hopping events from S 1 to S 0 . Almost all hopping events take place within 150 fs with a maximum peak at about 60 fs, in good agreement with experimental studies. ,, Moreover, it can be found that SPc and SPt have similar distribution for the S 1 → S 0 hopping times (see red vs blue in the right panel of Figure ).…”
Section: Resultssupporting
confidence: 65%
“…This exclusive stereospecific excited-state relaxation is seen in previous studies. 43,58,69 The right panel of Figure 5 depicts time distribution of all hopping events from S 1 to S 0 . Almost all hopping events take place within 150 fs with a maximum peak at about 60 fs, in good agreement with experimental studies.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 Many studied have verified that the nonadiabatic dynamics at the OM2/MRCI level is a powerful simulation tool in the description of excitedstate processes for media-sized and large polyatomic systems with the balance of computational accuracy and efficiency. [44][45][46][47][48][49] By following the excited-state molecular motions, we found that the protonation/deprotonation states of the pyrrole ring show the strong impact on the excited-state lifetime and reaction pathways. The underline reason is that the hydrogen bond network deeply modules the intramolecular motion, leading to different profiles of excited-state potential energy surfaces.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 95%
“…The photochemical isomerization of azobenzene and its derivatives has been reported in numerous experimental and computational papers in the past and in recent times. Some of these papers have reported combined experimental and theoretical results, as well.…”
Section: Introductionmentioning
confidence: 98%